Fish Farming Business Management Strategy Using the Business Model Canvas Method: An Islamic Economics Perspective - Afriyani, Nanda Syafira; Nasution , Juliana; Harahap , Muhammad Ikhsan (SENTRALISASI, 2025)
This study aims to analyze the management strategy of a fish farming business using the Business Model Canvas (BMC) approach and to review its practices from an Islamic economic perspective in Tanjung Rejo Village, Percut Sei Tuan District. The research employs a descriptive qualitative method, with data collected through interviews, observation, and documentation. As a novel contribution, this study integrates BMC and Islamic economics to provide a comprehensive analytical framework that connects business efficiency with ethical values. The findings indicate that while the existing BMC management is functional, there are significant weaknesses in the customer segments and distribution channels, leading to a strong dependence on middlemen (tengkulak). From an Islamic economics perspective, principles of justice, honesty, and social solidarity (tafakul ijtimāʿī) have been applied, but the primary challenge lies in the financing practices, which have the potential for riba. In conclusion, this research suggests that optimizing the business model and transitioning to equitable sharia financing are key to the sustainable development of the fish farming business. The practical implications of this study recommend diversifying products and markets, strengthening local partnerships like cooperatives, and providing access to sharia-compliant capital to support the independence of the fish farmers.